Pengembangan Urban Nutrigarden Sebagai Pemberdayaan Ekonomi Masyarakat Dengan Menggunakan Internet Of Things (Iot) - Erika Nurmatiani; Muhamad Ryanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Urban Nutrigarden is an activity of growing vegetables and herbs organically in an urban environment. The Urban Nutrigarden concept utilizes the space available at home, from the yard, vertical, roof of the house, to rocky soil. The Urban Nutrigarden concept in this community is environmentally friendly and sustainable. The purpose of cultivation is to obtain a balanced nutritional variation, form a sustainable ecosystem in the house and can improve economic improvement Encourage Microgreens cultivation partners to continue implementing the application of IoT technology to the Nutrigarden concept in their independent cultivation activities.